Cross-Dehydrogenative Coupling of Dithiolanes with Ketones and Indoles under Metal-Free Conditions - Singh, Kamal Nain; Singh, Paramjit; Singh, Pushpinder; Maheshwary, Yogita; Kessar, Satinder V.; Batra, Aanchal (Synlett, 2013)
A metal-free cross-dehydrogenative coupling of dithiolanes with ketones and indoles has been developed using DDQ as an oxidant. It provides an economical protocol for the synthesis of β-keto dithiolanes and 3-(1,3-dithiolan-2-yl) indoles.
Keywords: cross-dehydrogenative coupling; dithiolane; metal-free coupling; C–C bond; DDQ